(untitled) - Garber, Nicholas J. (Mason, OH, 2010)
The new edition of Garber and Hoel's best-selling text focuses on giving students insight into all facets of traffic and highway engineering. Students generally come to this course with little knowledge or understanding of the importance of transportation, much less of the extensive career opportunities within the field. Transportation is an extremely broad field, and courses must either cover all transportation modes or focus on specifics.
Keywords: Highway engineering,Đường cao tốc